PENGARUH TAYANGAN PROGRAM TALKSHOW RUMAH UYA DI TRANS7 TERHADAP PERILAKU ANTISOSIAL REMAJA DI KOTA PEKANBARU - Octaviandri, Reyhan; ", Rumyeni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The Program Talkshow Rumah Uya is a television program that discusses about the life of romance, friendship, and family. The problem raised in this program comes from the audience in the House who is more dominant about lovers couple's problems. Rumah Uya's program is packed with light, contemporary concept, and raises stories close to young people, indicating the program has teenage segmentation, so the program certainly has an influence on the antisocial behavior of the teenager. In The Cultivation Theory emphasizes how the impact achieved from a person when consuming media. The purpose of this research is to know whether there is influence between Impressions Program Talkshow Rumah Uya in Trans7 to Antisocial Behavior of Teenagers in Town Pekanbaru and how big influence between Impressions Program Talkshow Rumah Uya in Trans7 to Antisocial Behavior of Teenagers in Town PekanbaruThe method used in this research is quantitative explanative. The data were collected using questionnaires. The research was conducted at Pekanbaru City. The sample in this study amounted to 166 respondents. The sampling technique uses accidental sampling. The analysis test used in this research is simple linear regression analysis and to process the questionnaire data, done by using program SPSS for Windows version 20.The results obtained from simple linear regression analysis in this study is determination between Impressions Program Talkshow Rumah Uya in Trans7 to Antisocial Behavior Teens in Pekanbaru City and the amount of determination between Impressions Program Talkshow Rumah Uya in Trans7 to Antisocial Behavior Teenagers in Pekanbaru is equal to 22.6% which is categorized as weak, while the rest is influenced by other factors not present in this study.Keywords: Impressions, Talkshow, Rumah Uya, Antisocial Behaviour, Teenagers